2009
DOI: 10.1242/dev.027995
|View full text |Cite
|
Sign up to set email alerts
|

Tcf3 inhibits spinal cord neurogenesis by regulatingsox4aexpression

Abstract: The Lef/Tcf factor Tcf3 is expressed throughout the developing vertebrate central nervous system (CNS), but its function and transcriptional targets are uncharacterized. Tcf3 is thought to mediate canonical Wnt signaling, which functions in CNS patterning, proliferation and neurogenesis. In this study, we examine Tcf3 function in the zebrafish spinal cord, and find that this factor does not play a general role in patterning, but is required for the proper expression of Dbx genes in intermediate progenitors. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 51 publications
9
57
0
Order By: Relevance
“…In addition, we found that Tcf3 function in the regulation of gliogenesis is mediated independently of canonical Wnt signaling. Collectively, these results, together with previous reports (Gribble et al, 2009), suggest a novel function for Tcf3 in regulating the timing of neurogenesis and gliogenesis in the spinal cord.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, we found that Tcf3 function in the regulation of gliogenesis is mediated independently of canonical Wnt signaling. Collectively, these results, together with previous reports (Gribble et al, 2009), suggest a novel function for Tcf3 in regulating the timing of neurogenesis and gliogenesis in the spinal cord.…”
Section: Introductionsupporting
confidence: 81%
“…In this study, Tcf3 loss-offunction mediated by a morpholino oligonucleotide targeted against tcf3 (tcf3 MO) caused premature neurogenesis in the progenitors of the spinal cord. Since Tcf3 functions as a transcriptional repressor in the spinal cord, knock-down of tcf3 by an MO induces the expression of several tcf3 target genes including sox4a and sox11, which are normally repressed by Tcf3 (Gribble et al, 2009). These data suggest that constitutive repression of tcf3 target gene expression by a dominantrepressor form of Tcf3 may inhibit normal neurogenesis in the spinal cord.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…A critical event seems to be TCF3 phosphorylation by HIPK2 allowing one to derepress the target genes (Hikasa et al 2010;Sokol 2011), although in some cases TCF3 is likely to function in a Wnt-independent manner (Cole et al 2008;Gribble et al 2009). Homeodomain-interacting protein kinases (HIPKs) have been shown to function in a context-dependent manner in response to Wnt signaling (Wei et al 2007;Lee et al 2009;Louie et al 2009;Kim et al 2010).…”
Section: Regulation Of Tcf Protein Function During Axis Specificationmentioning
confidence: 99%
“…Although both TCF3 and TCF1 can bind b-catenin and Groucho corepressors Brantjes et al 2001), the two proteins appear to function very differently. TCF3 serves exclusively as a transcriptional repressor, whereas TCF1 is a transcriptional activator (Kim et al 2000;Gradl et al 2002;Houston et al 2002;Merrill et al 2004;Liu et al 2005;Nguyen et al 2006;Gribble et al 2009;Hikasa and Sokol 2011). Additional studies are needed to explain the difference in the activity of TCF1 and TCF3, which is likely caused by a distinct set of interacting partners.…”
Section: Regulation Of Tcf Protein Function During Axis Specificationmentioning
confidence: 99%